2019
DOI: 10.3389/fneur.2019.00236
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Enhances Gait in Cerebral Palsy: A Training Dose-Response Meta-Analysis

Abstract: Virtual-reality-based training can influence gait recovery in children with cerebral palsy. A consensus concerning its influence on spatiotemporal gait parameters and effective training dosage is still warranted. This study analyzes the influence of virtual-reality training (relevant training dosage) on gait recovery in children with cerebral palsy. A search was performed by two reviewers according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines on nine databases: PEDr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…21 Moreover, studies have reported enhancements in sensorimotor and cognitive performances after training with VR. [22][23][24] Recent neuroimaging studies too have reaffirmed these aspects, as VR-based interventions were shown to instigate neural plasticity. [25][26][27][28][29] In addition, other mechanisms that have been proposed to facilitate recovery using VR include enhanced biomechanical efficiency, real-time error feedback, 30,31 increased arousal, 32 and motivation.…”
Section: Introductionmentioning
confidence: 98%
“…21 Moreover, studies have reported enhancements in sensorimotor and cognitive performances after training with VR. [22][23][24] Recent neuroimaging studies too have reaffirmed these aspects, as VR-based interventions were shown to instigate neural plasticity. [25][26][27][28][29] In addition, other mechanisms that have been proposed to facilitate recovery using VR include enhanced biomechanical efficiency, real-time error feedback, 30,31 increased arousal, 32 and motivation.…”
Section: Introductionmentioning
confidence: 98%
“…It helps to sort out different neuropsychological issues for the treatment of the patient. [3][4][5] It is a useful tool for pain management where it is helpful to reduce the pain during treatment. The applications of this technology are emerging to provide a breakthrough for the treatment of phobia.…”
Section: Introductionmentioning
confidence: 99%
“…So far, VR-based therapies have been shown to induce cortical reorganization and promote the activation of different neuronal connections over a wide range of ages [7][8][9][10], leading to contrasted improvements in some motor and functional skills, such as gait or balance [11,12], while their potential contributions to the visual system remain virtually unexplored. Actually, most authors who have considered the study of VR interventions in relation to vision have focused their efforts on describing the short-and long-term ocular side effects associated with its use and on recreating different performance tests to try to identify common eye disorders or related impairments [13][14][15][16], with only a few who have attempted to use this tool to improve visual abilities that are not being adequately addressed by existing treatment options [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%